2005
DOI: 10.1016/j.ijom.2005.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric facial fractures: recent advances in prevention, diagnosis and management

Abstract: During the last 25 years, there have been considerable advances in the prevention, diagnosis and management of craniomaxillofacial injuries in children. When compared to adults, the pattern of fractures and frequency of associated injuries are similar but the overall incidence is much lower. Diagnosis is more difficult than in adults and fractures are easily overlooked. Clinical diagnosis is best confirmed by computed tomographic (CT) scans. Treatment is usually performed without delay and can be limited to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
296
5
36

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(373 citation statements)
references
References 100 publications
(205 reference statements)
36
296
5
36
Order By: Relevance
“…In similar series, Holland et al [8] reported that 3 % of children presenting to the emergency department with facial trauma, had a 2:1 male to female ratio. This was in accordance with earlier studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In similar series, Holland et al [8] reported that 3 % of children presenting to the emergency department with facial trauma, had a 2:1 male to female ratio. This was in accordance with earlier studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…The site and pattern of fracture depend upon the interrelationship between cause of injury, force of the injury and the unique anatomic features of the child's stage of development [11]. Our study shows the highest incidence of dentoalveolar injuries accounting for 40 % of maxillofacial trauma.…”
Section: Discussionmentioning
confidence: 67%
“…Decreased total blood and stroke volumes predispose them to greater risk of hypothermia, hypotension and hypoxia after blood loss [1].…”
Section: Discussionmentioning
confidence: 99%
“…At birth, the ratio between cranial volume and facial volume is approximately 8:1. By the completion of growth, this ratio becomes 2.5:1 [1]. This translates into higher percentage of cranial trauma in younger age group of less than 3 years and a shift to higher incidence of maxillofacial trauma in children after 3 years of age as facial growth starts to overtake the cranial growth due to developing dentition and sinus pneumatisation.…”
Section: Introductionmentioning
confidence: 99%
“…Among adolescents, an increase in risk-taking behaviour and a reduction in parental supervision result in an increase in the rate of facial fractures. Still, the overall incidence of facial fractures in the paediatric population is less than 15% of all facial fractures [4].…”
Section: Introductionmentioning
confidence: 99%